Antibiotic prophylaxis in breast cancer surgery. A randomized controlled trial - Prudencio,Rubens Murilo de Athayde (2020)
Abstract Purpose To assess the effect of antibiotic prophylaxis on surgical site infection (SSI) rates in women undergoing breast cancer surgery in two tertiary hospitals in Brazil. Methods This was a randomized, double-blind, placebo-controlled, parallel-group clinical trial. A total of 124 women without independent risk factors for SSI were randomly assigned to receive either cefazolin (antibiotic group, n = 62) or placebo (control group, n = 62) as preoperative prophylaxis. After surgery, all surgical wounds were examined once a week, for four weeks, according to the Centers for Disease Control and Prevention definitions and classifications for SSI. Results Baseline characteristics were homogeneous between the two groups. Only one patient in the antibiotic group developed SSI, which was classified as superficial incisional. The overall SSI rate was low, with no significant difference between groups. Conclusion Antibiotic prophylaxis had no significant effect on reducing SSI rates in women without independent risk factors for SSI undergoing breast cancer surgery.